2019
DOI: 10.22554/ijtel.v5i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of student academic performance using Moodle data from a Further Education setting.

Abstract: Increasingly educational providers are being challenged to use their data stores to improve teaching and learning outcomes for their students. A common source of such data is learning management systems which enable providers to manage a virtual platform or space where learning materials and activities can be provided for students to engage with. This study investigated whether data from the learning management system Moodle can be used to predict academic performance of students in a blended learning further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…A proprietary system uses an exclusive code where schools purchase a license or subscription to access and use the LMS features (Kimmons et al, 2019). Open-source systems use a free license with no cost where users have the freedom to access and use the system (Kimmons et al, 2019;Quinn & Gray, 2020;Turnbull et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A proprietary system uses an exclusive code where schools purchase a license or subscription to access and use the LMS features (Kimmons et al, 2019). Open-source systems use a free license with no cost where users have the freedom to access and use the system (Kimmons et al, 2019;Quinn & Gray, 2020;Turnbull et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Open-source systems use a free license at no cost where users have the freedom to access and use the system (Kimmons et al, 2019;Turnbull et al, 2019). Examples of open-source systems include Moodle, Wordpress, and Drupal (Kehrwald & Parker, 2019;Kimmons et al, 2019;Quinn & Gray, 2020).…”
Section: Nuances To Lms -Proprietary Vs Open-sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the k-Nearest Neighbor got better accuracy than the other. Quinn and Gray [20] used data from the Moodle to predict students 'grades whether they will succeed or fail in the course. They applied the classification algorithms Random Forest, Gradient Boosting, k-Nearest Neighbours and Linear Discriminant Analysis using R. They summarized that the use of data from Moodle gives the ability to early detection of students at risk.…”
Section: Related Workmentioning
confidence: 99%
“…Most institutions are having a hard time attracting new students due to more competitive educational practises [6]. Students' academic performance must be evaluated in order to encourage growth [7] and improve higher education quality. Numerous factors, including the student's socioeconomic background [8] and previous academic accomplishment, may have an impact on their academic performance, complicating the picture.…”
Section: Introductionmentioning
confidence: 99%